METAPHOR EXPRESSION IN FALL FOR YOU SONG LYRICS - Faidah Yusuf; Andi Reski Amelia (UIN Alauddin Makassar, 2018)
The purpose of this article is to analyze the type of metaphor and analyze the meaning in the lyrics of the song